Extent of application International Accounting Education Standard No. 4 ( Value And ethics And professional attitudes) In programs Accounting education University in Ghardaia (Journal of Economic Additions, 2020)
This study aims to find out the extent Applying the education standard IAS 4 (values and Ethics and professional attitudes) in accounting education programs at the university of Ghardaia. And to achieve the goals of the study was analyzed survey data from surveying which targeted the annual programs of the accounting departments during two phases Licentiate and Master degrees in university of Ghardaia, And through the results of this analysis we found that the student at the Licentiate degree studies only one standard it directly relates to the ethics of the accounting profession, called corruption and work ethics, and in the third year, there is none in all majors. But in the Master’s degree we find that the closest measure of the ethics of the accounting profession is the scale of the anti-corruption law, so that the latter fights corruption in all its forms, it is included in the program for all specializations during the first semester.key words: Accounting education, Accounting education programs, Ethics of the accounting profession.